Detection of Staphylococcus Aureus using quantum dots as fluorescence labels - Yaohua, Hu; Chengcheng, Wang; Bing, Bai; Mintong, Li; Wang, Ronghui; Li, Yanbin (International Journal of Agricultural and Biological Engineering, 2014)
Staphylococcus aureus (S. aureus) has been identified as one of the major foodborne pathogenic bacteria. The development of rapid detection methods for S. aureus is needed for assuring food safety. In this study, quantum dots were used as fluorescent labels in an immunoassay for quantitative detection of S. aureus. Firstly, biotin-labeled anti-S. aureus antibody was conjugated with streptavidin-coated magnetic nanobeads (180 nm diameter) and used to separate S. aureus cells. Then streptavidin coated quantum dots (QDs) were conjugated with biotin-labeled anti-S. aureus antibody and used as the fluorescence labels to mix with the separated S. aureus. Finally the fluorescence intensity of the bead-cell-QD complexes was measured at a wavelength of 620 nm. A linear relationship between S. aureus cell number (X) and fluorescence intensity (Y) was found for cell numbers ranging from 103 to 106 CFU (Colony Forming Unit)/mL, and the detection limit was 103 CFU/mL. The regression model can be expressed as Y = 7.68X + 35.06 with R2 =0.94. The detection of S. aureus in food sample was explored initially. The fluorescence intensity of food sample was close to the background, so it was not satisfied. Further study will focus on the application of the method for detection of S. aureus in food sample.